Effect of Crossbreeding on Fecundity, Growth Performance, and Heterosis of Black Tilapia, Red Tilapia, and Mozambique Tilapia Reared in Earthen Ponds in West Java, Indonesia - Robisalmi, Adam; Listiyowati, Nunuk; Pamungkas, Wahyu; Artati, Diah; Mustofa, Bisri; Malini, Desak Made (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research The crossbred performance of the four tilapia strains showed diverse heterosis values, with some being better, worse, or the same as their parents. Crossbred of black tilapia produced the best growth and fecundity performance. A hybrid of Mozambique tilapia and black tilapia showed the highest mid-parent heterosis value on growth traits but produced negative heterosis on fecundity, biomass, and survival traits. Crossbred of black tilapia and Mozambique tilapia have the potential to be used as candidates for cultivation and performance improvement through selection, although there are depressions and crossover advantages that are not prominent.     Abstract Increased tilapia production is challenged by genetic decline. Hybridization efforts for performance improvement through a selection of the best parent and strain pairs were a promising option. The objective of this study was to evaluate the crossing of black tilapia, red tilapia, and Mozambique tilapia against the performance of fecundity, growth, and survival and estimate the value of heterosis. The experimental design used a completely randomized design with 3 replications with the treatment of different populations of crosses. The rearing activities were carried out in earthen ponds for 150 days with a stocking density of 10 fish/m2. The parameters observed included egg fecundity, growth, survival, and the value of heterosis. The results showed that the fecundity and growth values of crossbred black tilapia were significantly higher than others (p<0.05). The highest survival rate was shown by crossing pure strains of red tilapia. The hybrid of Mozambique tilapia and black tilapia (♀ MJ x ♂ NW) showed the highest mid-parent heterosis value on growth characters but produced negative heterosis on characters, fecundity, biomass, and survival. Overall, the crossbred of black tilapia (♀BS x ♂ NW) performed better than the inbred strains, with positive mid-parent heterosis in all characters measured. These results indicate that crossbreeding has the potential to be used as a candidate for cultivation and performance improvement through selection, although there were depressions, and the superiority of the crosses was not prominent.